Evaluation of Critical Illness Polyneuropathy/Myopathy in Pediatric Intensive Care Unit - Didar Arslan; Rıza Dinçer Yıldızdaş; Özden Özgür Horoz; Nagehan Aslan; Yasemin Çoban; Şakir Altunbaşak; Mehmet Balal; Zeliha Haytoğlu (Galenos Yayinevi, 2020)
Introduction:The aim of this study was to determine the frequency of patients with critical illness polyneuropathy/myopathy followed by mechanical ventilator in the intensive care unit, and to determine the risk factors associated with this condition and discuss them with the literature.Methods:This study was performed retrospectively (August 2012 to August 2017), at a tertiary university hospital in Turkey. A total of 31 patients who were on mechanical ventilation and diagnosed with polyneuropathy/myopathy by electroneuromyography (ENMG) during pediatric intensive care unit follow-up were included in the study. Data were collected from patient files and computer system. Demographic characteristics of the patients, causes of hospitalization, underlying disease, length of the pediatric intensive care unit and hospital stay, length of mechanical ventilation, and treatment modalities were recorded. Patients without respiratory support and patients on mechanical ventilation without ENMG procedures were excluded.Results:A total of 31 patients were included in the study. Myopathy was present in 5/31 (16.1%) and polyneuropathy in 26/31 (83.9%) patients. Respiratory distress/failure was the most common cause of respiratory support (n=10, 32.3%) and the second most common cause was post cardiac surgery (n=9, 29%). The diagnosis of 18 (58%) patients were sepsis and 2 (6.4%) patients had multiple organ failure. The mean duration of mechanical ventilation was 27.4±14.1 days, length of pediatric intensive care unit stay was 41.5±24 days, length of hospital stay was 57.5±27.5 days. Mortality was observed in 5 (16.1%) of 31 patients.Conclusion:Critical illness polyneuropathy and myopathy in intensive care practice is a condition with increasing frequency and importance. Increased attention to this matter allows to take the necessary preventions, early recognition and to make the appropriate approach.